Oxytocin administration enhances controlled social cognition in patients with schizophrenia - Woolley, J.D. (Psychoneuroendocrinology, 2014)
BACKGROUND: Individuals with schizophrenia have functionally significant deficits in automatic and controlled social cognition, but no currently available pharmacologic treatments reduce these deficits. The neuropeptide oxytocin has multiple prosocial effects when administered intranasally in humans and there is growing interest in its therapeutic potential in schizophrenia. METHODS: We administered 40 IU of oxytocin and saline placebo intranasally to 29 male subjects with schizophrenia and 31 age-matched, healthy controls in a randomized, double-blind, placebo-controlled, cross-over study. Social cognition was assessed with The Awareness of Social Inference Test (TASIT) and the Reading the Mind in the Eyes Test (RMET). We examined the effects of oxytocin administration on automatic social cognition (the ability to rapidly interpret and understand emotional cues from the voice, face, and body); controlled social cognition (the ability to comprehend indirectly expressed emotions, thoughts, and intentions through complex deliberations over longer time periods); and a control task (the ability to comprehend truthful dialog and perform general task procedures) in individuals with and without schizophrenia using mixed factorial analysis of variance models. RESULTS: Patients with schizophrenia showed significant impairments in automatic and controlled social cognition compared to healthy controls, and administration of oxytocin significantly improved their controlled, but not automatic, social cognition, F(1, 58) = 8.75; p = 0.004. Conversely, oxytocin administration had limited effects on social cognition in healthy participants. Patients and controls performed equally well and there were no effects of oxytocin administration on the control task. DISCUSSION: Intact social cognitive abilities are associated with better functional outcomes in individuals with schizophrenia. Our data highlight the potentially complex effects of oxytocin on some but not all aspects of social cognition, and support the exploration of intranasal oxytocin as a potential adjunct treatment to improve controlled social cognition in schizophrenia. Published by Elsevier Ltd.